Research universities in Malaysia: What beholds? / Nooraini Mohamad Sheriff and Noordini Abdullah - Mohamad Sheriff, Nooraini; Abdullah, Noordini (Penerbit UiTM (UiTM Press), 2017)
The National Higher Education Strategic Plan Beyond 2020 aims at further strengthening Malaysian research universities and envisions that two Malaysian universities will be among the Top 100 world universities. To date there are 5 research universities in Malaysia, namely University of Malaya (UM), Universiti Kebangsaan Malaysia (UKM), Universiti Sains Malaysia (USM), Universiti Putra Malaysia (UPM) and Universiti Teknologi Malaysia (UTM) being the latest addition. These research universities are required to focus primarily on research and innovation activities, driven by highly competent academics and competitive student admissions. Research universities too are expected to explore their intellectual capacity and become models of Malaysian universities in conducting research activities aimed at knowledge advancement. Apart from this research universities are entrusted to generate their own income and establish holding companies responsible for conducting business ventures through the commercialization of their research products. Quality and quantity of researchers, research and postgraduates are also expected to increase in these research driven institutions. This calls for a visionary university leadership and the application of a new image and organizational principles. Education, training and employment policies too have to be reviewed, to ensure staff have the skills necessary for the development of research activities.